نحو نموذج للتنبؤ بتعثر الشركات المقترضة من البنوك التجارية العاملة في الجزائر حالة البنك الوطني الجزائري، بنك الجزائر الخليج، بنك Natixis - قارة عشيرة, نصر الدين; حبار, عبد الرزاق (University of Eloued جامعة الوادي, 2019)
نهدف من خلال هذه الدراسة إلى بناء نموذج للتنبؤ بفشل الشركات المقترضة من البنوك التجارية العاملة بالجزائر، اعتمدنا على بيانات تتمثل في 17 نسبة مالية مستخرجة من القوائم المالية لعينة مكونة من 35 شركة خلال الفترة 2006 - 2015 ، وتتضمن 23 شركة سليمة و 12 شركة متعثرة، وباستعمال أسلوب التحليل التمييزي قمنا ببناء نموذج للتنبؤ بالفشل يتكون من 13 متغير حقق نسبة تنبؤ صحيح بلغت Abstract: The purpose of this paper is to build a model for predicting the failure of borrowing corporations from commercial banks in Algeria. The data used in this study is 17 financial ratio obtained from the financial statements of the sample (35 corporates during the period 2006-2015). The sample is based on 12 failed companies and 23 non failed companies, by using the Discriminant Analysis method, we have built a model for predicting failure consists of 13 variables, this model have made a correct prediction rate amounts to 71.43 percent
Towards a model for predicting the failure of corporate borrowers from commercial banks in Algeria: Cases of BNA, AGB, NATIXIS Bank
مقال - مجلة رؤى اقتصادية
Keywords: منح الائتمان؛ خطر التعثر؛ تنبؤ بتعثر الشركات؛ تحليل تمييزي؛ نسب مالية. الترميز الاقتصادي ) JEL :) G11, G21, G24, C61; Credit granting, Failure risk, Prediction of corporate failure, Disciminant analysis, Finantial ratios. Jel Classification Codes : G11, G21, G24, C61